Prof. Yin Li: 100−1=0—every step during esophageal surgery should strive for perfection - Yuan, Amber (Journal of Thoracic Disease, 2018)
The Third Ruijin International Thoracic Surgery Symposium was successfully held in Shanghai from 15th to 16th of November in 2018, gathering many renowned experts and scholars from the frontier field at home and abroad to discuss the latest progress and hot issues in thoracic surgery.